Surgical treatment of progressive cauda equina compression caused by spontaneous spinal subdural hematoma: A case report. Issue 12 (March 2019) - Li, Xigong; Yang, Ge; Wen, Zhiqiang; Lou, Xianfeng; Lin, Xiangjin
Abstract: Rationale: Spontaneous spinal subdural hematoma (SSDH) without an underlying pathology is a very rare condition. The treatment protocol for SSDH is early diagnosis and treatment before irreversible damage to neural tissue. However, there is no agreement on the etiopathogenesis, as well as the need for surgery to treat spontaneous SSDH. Here, we report a rare case of spontaneous SSDH with progressive deterioration and symptoms of cauda equina syndrome after ineffective conservative treatment. Patient's concern: A 38-year-old male patient presented with sudden lower back and bilateral leg pain. Diagnosis: A magnetic resonance imaging (MRI) scan on the third day after the onset of symptoms revealed a subdural hematoma from L1 to S1, presenting as hyperintensities on T1 weighted sequences and hypointensities to isointensities on T2 weighted sequences. Intervention: Laminectomy and subdural evacuation were performed immediately. Outcomes: An abnormal ligamentum flavum was observed intraoperatively. A histological examination revealed extravasation of blood in the degenerated ligamentum flavum. Postoperatively, the lower limb pain improved immediately. At the 6-month follow-up, the pain and numbness of the lower limb disappeared, and the muscle strength of both legs recovered completely with normal gait. Lessons: Spontaneous SSDH with ligamentum flavum hematoma was caused by a sudden increase of intravenous pressure, resulting from a marked surge in the intra-abdominal or intrathoracic pressure. Consecutive MRI scans provided valuable information, leading to a diagnosis of spontaneous SSDH. The treatment protocol for spontaneous SSDH should be determined based on the location and stage of the hematoma, as well as the subject's neurological status. Abstract : Supplemental Digital Content is available in the text